2006
DOI: 10.1093/fampra/cmi109
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from recruiting young female students to a randomised controlled trial of chlamydia screening

Abstract: For a study on a sensitive topic, two researchers recruiting women in groups after lectures may be a more effective and cost-effective way than individual recruitment by researchers working alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Although numerous studies have evaluated the effectiveness of various recruitment strategies, to our knowledge few have focused on the effectiveness of group seminars for increasing recruitment. One research team found group information sessions to be a more efficient and cost effective recruitment strategy than individual sessions when recruiting female university students for a community-based trial of chlamydia screening to prevent pelvic inflammatory disease [ 6 ]. Another team found group meetings with families to be a useful strategy for recruiting children to RCTs, where parents must provide consent [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have evaluated the effectiveness of various recruitment strategies, to our knowledge few have focused on the effectiveness of group seminars for increasing recruitment. One research team found group information sessions to be a more efficient and cost effective recruitment strategy than individual sessions when recruiting female university students for a community-based trial of chlamydia screening to prevent pelvic inflammatory disease [ 6 ]. Another team found group meetings with families to be a useful strategy for recruiting children to RCTs, where parents must provide consent [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Participants are asked to complete a consent form and questionnaire, and to provide a self-taken lower vaginal swab. They are given a small non-monetary gift in return.…”
Section: I-mentioning
confidence: 99%
“…4 Ciprofloxacin treatment of intermediately resistant cases has a failure rate of 8%, which rises to 60% in fully resistant cases. 6 The data show the importance of ongoing surveillance of susceptibility trends, in particular to modify treatment guidelines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment is one of the most challenging tasks for investigators conducting clinical trials (Harris et al, 2003; Ivaz et al, 2006; Villarruel et al). Others have cited recruitment and retention of study participants as major concerns for any health-related research examining outcomes of treatment (Hough, Tarke, Renker, Shields, & Glatstein, 1996).…”
mentioning
confidence: 99%